Understanding the Role of Sports Injury Management by Australian Osteopaths: A Cross Sectional Survey of 992 Practitioners - Brett Vaughan; Jon Adams; Wenbo Peng; Lauren V. Fortington; Michael Fleischmann; Kylie Fitzgerald; Amie Steel; David Sibritt (Applied Sciences)
Sport-related injuries are common presentations to primary care and hospital settings. Australian osteopaths practice mainly in private clinical settings in which the frequency of sport-related injury presentations, and how these injuries are managed, is unknown. The objective of the study was to describe the demographic, practice, and clinical management characteristics of Australian osteopaths who report often treating sport-related injuries. The study is a secondary analysis of data derived from the Australian osteopathy practice-based research network. Respondents indicated the frequency treating sports-related injuries in addition to other demographic, practice, and patient management characteristics. Backward logistic regression identified significant characteristics associated with often treating sport injuries. Over half (51%) of a nationally representative sample of Australian osteopaths reported treating sport-related injuries often. Those osteopaths who treat sports injuries often were likely to be male (p < 0.01) and utilise exercise prescription (OR2.34) and sports taping (OR5.99). Australian osteopaths who often treat sports-related injuries provide advice to patients and use exercise prescription more frequently than osteopaths who do not treat these injuries often. The data in the current work begin to explore how osteopaths manage sports-related injuries and highlights how they may be able to provide sports injury care for both recreational and elite sport populations.